Pola Pengembangan Pembelajaran Bahasa Indonesia untuk Anak Autisme - Yunaika, Weti (Absorbent Mind, 2023)
The aim of this research is to analyze the development patterns of Indonesian language learning for children with autism. This type of research is a literature review. Data collection method with documentation from Google Scholar. Data analysis using a systematic literature review. The pattern of developing Indonesian language learning for children with autism needs to be prepared with a special approach that takes into account their individual characteristics and needs. It is important to align learning strategies with the sensory preferences of children with autism, such as the use of visuals and repetition of material. Technology integration can be an effective tool to facilitate learning, while observing a clear and consistent structure in teaching. Support from teachers and an inclusive environment are also key elements in creating learning patterns that support the progress of Indonesian in children with autism.